“In Black and White, I’m A Piece of Trash:” Abuse, Depression, and Women's Pathways to Prison - Adamo Valverde, Alexa (2016)
Women’s lived experiences of abuse and depression are examined within the context of gendered and racialized pathways to incarceration among 403 women randomly selected from a diagnostic unit in a state prison. This study utilizes feminist action research and community psychological methods to understand what factors predict incarcerated women’s placement on the mental health caseload and provides quantitative support for the pathways theoretical framework. Findings indicate that, among the sample, the prevalence of abuse experiences prior to incarceration exceeded 90%, prevalence of mental health problems exceeded 70%, and less than 35% were receiving mental health care. Being Caucasian, experiencing depression and suicidal ideation, and serving time for certain types of (non-violent, non-property, and non-drug related) crime (e.g., cruelty to children, prostitution, public order, “technicals,” and others) predicted the placement of women on the mental health caseload. Implications for trauma-informed, anti-racist, gender-responsive policies and interventions are discussed